Thoracoscopic management of a giant horseshoe shaped oesophageal leiomyoma: a case report - Arunachalam, Kirthika; Sanniyasi, Saravanan; Iyyappan, Ponniah; Kanthan Pandian, Sri Lakshmi (International Surgery Journal, 2025)
Benign oesophageal tumours are considered rare, and most common are leiomyomas with the incidence of 0.005%. Many cases are asymptomatic, up to 15%–50%, and most cases are discovered incidentally. These may vary in size but are typically smaller than 3 cm. Giant esophageal leiomyoma is defined as tumour greater than 10 cm in diameter. Traditionally, open thoracotomy and enucleation have been the primary treatment modalities for oesophageal leiomyoma. However, in recent years, video-assisted thoracoscopic surgery (VATS) enucleation has gained recognition for its proven advantages as a minimally invasive surgical option. Herein we present our experience with patient presenting with cough rather than dysphagia as a main symptom, who was diagnosed to be having giant oesophageal leiomyoma. VATS guided enucleation was accomplished successfully. Size of lesion was 10.0×8.0×7.0 cm. Postoperative recovery was uneventful.